DOMINANCE AND HEGEMONY: A STUDY OF MARXIST CLASS CONFLICT IN MOHSIN HAMID’S MOTH SMOKE - Javed Ashiq; Dr. Tariq Usman; Fazal Rabi; Uzma (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistani Anglophone literature chiefly deals with social life of Pakistan and the social conditions of diaspora in the western world. All social life revolves around economy. It is the production, reception, and distribution of wealth that determines actions of the people. The study examines economic conditions and class conflict as portrayed by Hamid in his novel Moth Smoke. The selected text bears vivid pictures of class conflict and its impact on the lives of the characters. All clashes in a society spring, says Marx (1995) from wealth, its fair or unfair distribution. Marxist critique examines how writers incorporate social and historical contexts into their works. The novel has several overt instances involving covert settings. Marxist critics identify overt occurrences and connect them to covert events of the moment. Characters in the novel, Moth Smoke’s protagonist Daru and an unnamed youngster, experience economic hardship due to Pakistan’s economic down turn. This study follows Barry’s (1995) technique of studying Marxist analysis. To address class issues such as elite dominance over lower-class individuals and unequal employment prospects, To address other societal concerns in Pakistan, such as corruption, unemployment, poverty, drug use, and lack of quality education. The study reveals that the central as well as the marginal characters are deeply influenced by their economic conditions and it also determines their actions that lead to their happy or unhappy life.